Law and authority under the guise of the good - Rodríguez Blanco, Verónica (Oxford : Hart Publishing, 2014)
The book argues that an understanding of the nature of legal normativity involves an understanding of the nature and structure of practical reason in the context of the law, and advances the idea that legal authority and normativity are intertwined.
Introduction -- Legal authority and normativity : rediscovering a hidden relationship -- Law as an actuality -- The guide of the good model -- Understanding the nature and structure of practical reason : excavating the classical tradition -- A defence of the parastic thesis : a re-examination of Hart's internal point of view -- A defence of the parastic thesis II : does Kelsen's notion of legal normativity rest on a mistake? -- Authorities' claims as expressions of intentions -- Authority and normativity : a defence of the "ethical-political" account of legal authority -- The epistemology of modestly objective values and robust value realism -- Possible objections and concluding note.
Obsahuje bibliografii a rejstřík
Elektronická reprodukce.
Keywords: právní filozofie; právo; autorita; philosophy of law; law; authority; e-knihy online; e-books online